A SYSTEMATIC REVIEW OF DIAGNOSIS AND TREATMENT OPTIONS FOR TINEA IMBRICATA: Life Science-Dermatology - ABDULAZEEM AL-BASSAM, RANA; SALEM AL AFARI, BASMAH; HASSAN MOHAMED SALEM, MANAL (International Journal of Life Science and Pharma Research, 2019)
Tinea imbricata is a cutaneous fungal disease and sometimes called (Tokelau). The causative agent is a dermatophyte known as Trichophyton concentricum. It is an endemic in developing countries particularly in South Pacific, India, Central and South America, as well as Mexico. It is generally observed in people with poor living conditions and poor personal hygiene. Predisposing factors are hot weather, humidity, and host immunity in addition to genetic factors. The patients usually presented with concentric or lamellar skin lesions. The aim of this review is to highlight important information about microbial, clinical and therapeutic aspects of tinea imbricta. In this review, we search the literature to identify articles talking different aspects of tinea imbricta. The electronic search was performed in four databases to identify eligible articles in the literature. Electronic databases were searched including MEDLINE and EMBASE using PubMed search engine. In addition, Cochrane library and ovid was searched. The titles and abstracts of the resulted articles were screened to identify eligible studies. Based on the primary screening results the irrelevant studies, duplicated and reviews were excluded. Tinea imbricta is found to be endemic in 3 main geographical regions, Southwest Pacific, Southeast Asia, and Central and South America. There is an autosomal recessive genetic factor which increases the vulnerability to tinea imbricta infection. The levels of both general and specific IgE class antibodies were higher than normal values. Usual clinical findings of tinea imbricta are multiple annular, concentric, squamous sores and may be associated with erythema. The infection usually starts in young people on the facial region and disseminate to the trunk, arms or legs.The eradication of the disease has not been possible yet, thus preventative procedures should be adopted as a strategy of disease control.